Histological Change of Placenta in Diabetic Pregnant Women in Comparison to Normal Pregnant Women (East West Medical College Journal, 2024)
Background: The placenta is a foeto-maternal organ and its alterations is directly related to the disease’s length and severity. The human placenta experiences a number of functional and structural pathologic alterations when complicated by metabolic disorder such as diabetes mellitus. Methods: This cross-sectional comparative study was conducted over a period of threeyears from January 2019 to December 2021 at the Department of Anatomy, Rajshahi Medical College, Rajshahi, in collaboration with the Department of Obstetrics and Gynaecology, Rajshahi Medical College Hospital and Diabetic Hospital Rajshahi, Bangladesh. The study was carried out on 70 pregnant women, among them 35 diabetics and 35 non-diabetics. The fibrinoid necrosis, syncytial knot and immature villi of the placenta were studied in diabetic and non-diabetic pregnant women. SPSS software, version-24 was used for data analysis, with a p-value < 0.05 indicating statistically significance for all tests. Results: The diabetic and non-diabetic pregnant women groups were almost identical in terms of attachment of umbilical cord to placenta with marginal attachment being more often found in either group (p = 0.829). Histological examination of placenta showed that fibrinoid necrosis was common in placenta of diabetic mothers than that of the normal mothers (p < 0.001). Syncytial knot and immature villi were higher in the former group than those in the latter group, here p values were also less than .001. Conclusion: Histological findings (fibrinoid necrosis, syncytial knot and immature villi) were more in placenta of diabetic mother and they were highly significant different between the groups.EWMCJ Vol. 12, No. 1&2, January-July 2024: 27-33